A Design-based Research of an Oceanography Module as a Part of the Israeli High School Earth Sciences Program - Orion, Nir; Cohen, Carmit (Journal of Geography Education, 2007)
This study is a Design-based Research type that was conducted in order to develop a new module: "Oceans and the Earth systems" as part of the environmental-based interdisciplinary component of the Israeli high school earth science curriculum. The study included three spiral cycles of development-implementation-research and the collection of the data was based on a battery of both qualitative and quantitative research tools. The sample included about 120 students from 8 classes from five different schools. The design-based research method enables to identify the strengths and the weaknesses of the curriculum in order to modify the curriculum. It was repeatedly found throughout the three development cycles that the interest of students in oceanography topics is high. The students have increased their knowledge significantly and undergone through a meaningful conceptual change. The students’ achievements and attitudes correlated positively with the implementation of inquiry based learning in the lab and the outdoor learning environments, and the ability of the students to choose what they would like to study - all of it or at least part of it. Following our results it is suggested that the earth systems approach could serve as a powerful platform in motivating students to study complicated scientific concepts and processes from all the scientific disciplines.